2021
DOI: 10.3390/foods10112678
|View full text |Cite
|
Sign up to set email alerts
|

SlCCD1A Enhances the Aroma Quality of Tomato Fruits by Promoting the Synthesis of Carotenoid-Derived Volatiles

Abstract: The loss of volatiles results in the deterioration of flavor in tomatoes. Volatiles are mainly derived from fatty acid, carotenoid, phenylpropane, and branched chain amino acids. In this study, the tomato accession CI1005 with a strong odor and accession TI4001 with a weak odor were analyzed. The volatile contents were measured in tomato fruits using gas chromatography-mass spectrometry. The scores of tomato taste and odor characteristics were evaluated according to hedonistic taste and olfaction. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Free astaxanthin lacks fatty acids and therefore cannot be degraded to aldehydes and alcohols. 6‐Methyl‐5‐hepten‐2‐one was detected in FA and DA, following thermal degradation of astaxanthin (Cheng et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Free astaxanthin lacks fatty acids and therefore cannot be degraded to aldehydes and alcohols. 6‐Methyl‐5‐hepten‐2‐one was detected in FA and DA, following thermal degradation of astaxanthin (Cheng et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It imparted a fresh floral and sweet aroma to goji wine. Limonene had a slightly citrus aroma and was the modifier compound for GW3 (Cheng et al, 2021). Thus, these compounds imparted goji wine a fresh floral and fruity aroma in general, accompanied by woody aromas and had the typical characteristics of wine.…”
Section: Effect Of Degradation Treatment On Volatile Compounds Of Goj...mentioning
confidence: 98%
“…All carotenoids degraded under the combined influence of photolysis and OH scavenging and the major degradation products were apo-aldehydes and apo-ketones (Semitsoglou-Tsiapou et al, 2022). Cheng et al (2021) reported that the accumulation of norisoprenoid volatiles is regulated by carotenoid cleavage oxygenases (CCDs). In addition, these carotenoid-derived volatile compounds have floral, fruity, fatty, and sweet-like flavors, which greatly enhance the quality of the aroma of goji wine (Simkin, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Simkin et al. (2004) observed that the downregulation of the LeCCD1A and LeCCD1B genes using an antisense construct in tomato resulted in a significant reduction in the rates of emission of geranylacetone and β-ionone in cut tomato fruits, but did not affect the overall carotenoid content ( Simkin et al., 2004 ; Cheng et al., 2021 ; Simkin, 2021 ). This suggests that additional enzymes may be involved in carotenoid cleavage.…”
Section: Pathways For Synthesis Of Tomato Volatilesmentioning
confidence: 99%